2012
DOI: 10.1097/scs.0b013e31825aaa03
|View full text |Cite
|
Sign up to set email alerts
|

Incisions for Orbital Floor Exploration

Abstract: Incisions used for orbital floor exploration continues to remain a topic of controversy. Historically, 3 incisions have been used for orbital floor repair: transconjunctival, subciliary, and subtarsal. Past studies have attempted to stratify the superiority of one incision over the others. Insufficient level of evidence and inconsistent methodology have lead to inconclusive data. Our authors performed a systematic review of literature to assess the quality of evidence in literature and recommend guidelines for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
2
35
0
5
Order By: Relevance
“…Subciliary approaches have been associated with much higher complication rates and 12.9% of cases result in ectropion. 8 Subtarsal approach is associated with less ectropion and depending on its correct placement, conspicuous scar rates are low, around 1 to 3%. [9][10][11] The preference for most surgeons is a transconjunctival approach of the orbital floor due to its very low complication rates (less than 1% in several series) and absence of a visible scar.…”
Section: Discussionmentioning
confidence: 99%
“…Subciliary approaches have been associated with much higher complication rates and 12.9% of cases result in ectropion. 8 Subtarsal approach is associated with less ectropion and depending on its correct placement, conspicuous scar rates are low, around 1 to 3%. [9][10][11] The preference for most surgeons is a transconjunctival approach of the orbital floor due to its very low complication rates (less than 1% in several series) and absence of a visible scar.…”
Section: Discussionmentioning
confidence: 99%
“…Fraktürün geliştiği duvar ve yerleşimine göre cilt insizyonu, transkonjonktival, subtarsal veya mediyal duvar için transkarünküler orbitotomi gibi seçe-nekler mevuttur. [18][19][20] Han ve ark., mediyal ve alt duvar fraktürünün birlikte görüldüğü hastalarında, bir gruba sadece subsiliyer cilt insizyonu, bir gruba da subsiliyer cilt insizyonuna ek olarak transkarünküler yaklaşımla çift insizyon yaptıklarını, çift insizyonla fraktür bölgesini daha iyi vizüalize ettiklerini, ancak başarı açısından iki grup arasında fark saptamadıklarını bildirmişlerdir. 21 Cerrahi yaklaşımımızı; fraktür bölgesi, fraktürün büyük-lüğü ve etkilediği duvar sayısı, cilt kesisinin olup olmadığı, kesinin düzgün olup olmadığına göre belirledik.…”
Section: Discussionunclassified
“…61 The subtarsal incision offers direct orbital floor access and is less techni cally demanding, but may leave visible scarring. 60 A recent comprehensive review of incision techniques found insufficient highlevel evidence to suggest one pattern over another, but did show a low incidence of complications with transcon junctival approaches, the highest rate of complica tions and revisions in subciliary approaches, and the lowest revision rate with subtarsal incisions. 60 It should be noted that the transcaruncular inci sion pattern may be associated with increased ophthalmic complications, including nasolacri mal obstruction caused by scar tissue formation.…”
Section: Methods Of Repair Incision Patternsmentioning
confidence: 97%
“…60 A recent comprehensive review of incision techniques found insufficient highlevel evidence to suggest one pattern over another, but did show a low incidence of complications with transcon junctival approaches, the highest rate of complica tions and revisions in subciliary approaches, and the lowest revision rate with subtarsal incisions. 60 It should be noted that the transcaruncular inci sion pattern may be associated with increased ophthalmic complications, including nasolacri mal obstruction caused by scar tissue formation. 62 Although the rates of reported complications are low and this incision pattern is gaining in popular ity, it is not currently in widespread use.…”
Section: Methods Of Repair Incision Patternsmentioning
confidence: 97%
See 1 more Smart Citation